Mechanism of Alkyl Chloroformate-Mediated Esterification of Carboxylic Acids in Aqueous Media - Opekar, Stanislav; Kvíčala, Jaroslav; Moos, Martin; Pejchal, Vladimír; Šimek, Petr (The Journal of organic chemistry, 2021)
The protection of carboxyl groups by esterification has been the most common method in macroscale and microscale chemistries. The esterification is usually conducted under anhydrous conditions; however, in biological chemistry and related fields, the reaction is of major concern in aqueous environments. Immediate esterification of the carboxyl in aqueous alcoholic media driven by an alkyl chloroformate and pyridine has been such a method which has found widespread use in many research and industrial laboratories. Nevertheless, the reaction mechanism has not yet been investigated, to our knowledge, and is not well understood. Herein, we describe the reaction intermediates and demonstrate that the reaction proceeds via a continual formation of the N-acylpyridinium intermediate decomposed by several reaction channels to the final ester. The understanding of the mechanism could encourage novel laboratory applications of this important esterification method.
Keywords: kyseliny karboxylové; Esters; esterifikace; estery; Carboxylic Acids; Water; voda; Esterification